Impact of Lemongrass and Peppermint Essential Oils Supplementation on the Growth Performance and Carcass Traits of Japanese Quails - Srivastava, Siddhartha; Palod, Jyoti; Sharma, Rabendra K.; Kumar, Shive; Anita; Kumar, Ripusudan; Singh, Manoj K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
An experiment was conducted on 150, six-day-old Japanese quails for 5 weeks to study the impact of lemongrass and peppermint essential oils supplementation on the growth performance and carcass traits. Experimental Japanese quail chicks were randomly allocated into 5 different treatment groups (T0, T1, T2, T3 and T4) with three replicates of 10 chicks each. Different treatment groups were supplemented with essential oils, viz. T0 control basal diet (no essential oil), T1 0.1% lemongrass essential oil, T2 0.1% peppermint essential oil, T3 0.05% lemongrass + 0.05% peppermint essential oils, and T4 0.1% lemongrass + 0.1% peppermint essential oils in the feed. The influence of lemongrass and peppermint essential oils supplementation on body weight gain (BWG), feed intake (FI), feed conversion ratio (FCR), performance index, the protein efficiency ratio (PER), production efficiency factor, and carcass characteristics were assessed during the experiment. Results indicated that the inclusion of lemongrass and peppermint essential oils increased body weight gain, reduced feed intake, improved feed conversion ratio, performance index, protein efficiency ratio, and production efficiency factor, with best performance during all the periods was noted in the T3 group. Lemongrass and peppermint essential oils at 0.05% each in combination significantly (p <0.05) improved dressed yield with and without giblets, cut-up parts in terms of thighs, breast, drumsticks, wing weights, weights of heart, gizzard, and giblets. In any treatment group, the liver weight and processing losses were not significantly affected by lemongrass and peppermint essential oils supplementation.